New Record of Fungal Infection -Fusarium SP. In the Culture of Land Slug Laevicaulis alte (Ferussac) - a Severe Pest of Azadirachta indica (Neem) Seedlings in Rajasthan and Gujarat - Kumar, Seema; Srivastava, K. K.; Ullah, Ameen (Indian Forester, 1998)
No abstract